How families matter for understanding economic inequality - Cézar Santos; Michele Tertilt (Inter-American Development Bank (IDB), 2023)
In this paper we discuss the importance of families for understanding economic inequality. Family structure can in principle be an amplifier or mitigator of economic inequality. We describe three channels on how families shape economic inequality. First, how people match to form families matters for inequality across families. Second, parental investments in children can amplify existing inequalities across generations. Third, inequality can exist even within families, and the economic environment can shape inequality in consumption and leisure between spouses. In this survey we describe these channels and discuss the related literature.
Keywords: D13; J12; J13; J16; 330; Families; Inequality; Marriage; Children